Inflammaging, immunosenescence, and cardiovascular aging: insights into long COVID implications - Müller, Ludmila; Di Benedetto, Svetlana (Frontiers in Cardiovascular Medicine, 2024)
Aging leads to physiological changes, including inflammaging—a chronic low-grade inflammatory state with significant implications for various physiological systems, particularly for cardiovascular health. Concurrently, immunosenescence—the age-related decline in immune function, exacerbates vulnerabilities to cardiovascular pathologies in older individuals. Examining the dynamic connections between immunosenescence, inflammation, and cardiovascular aging, this mini-review aims to disentangle some of these interactions for a better understanding of their complex interplay. In the context of cardiovascular aging, the chronic inflammatory state associated with inflammaging compromises vascular integrity and function, contributing to atherosclerosis, endothelial dysfunction, arterial stiffening, and hypertension. The aging immune system's decline amplifies oxidative stress, fostering an environment conducive to atherosclerotic plaque formation. Noteworthy inflammatory markers, such as the high-sensitivity C-reactive protein, interleukin-6, interleukin-1β, interleukin-18, and tumor necrosis factor-alpha emerge as key players in cardiovascular aging, triggering inflammatory signaling pathways and intensifying inflammaging and immunosenescence. In this review we aim to explore the molecular and cellular mechanisms underlying inflammaging and immunosenescence, shedding light on their nuanced contributions to cardiovascular diseases. Furthermore, we explore the reciprocal relationship between immunosenescence and inflammaging, revealing a self-reinforcing cycle that intensifies cardiovascular risks. This understanding opens avenues for potential therapeutic targets to break this cycle and mitigate cardiovascular dysfunction in aging individuals. Furthermore, we address the implications of Long COVID, introducing an additional layer of complexity to the relationship between aging, immunosenescence, inflammaging, and cardiovascular health. Our review aims to stimulate continued exploration and advance our understanding within the realm of aging and cardiovascular health.